Auditory function in children with Charcot-Marie-Tooth disease - Rance, G.; Ryan, M. M.; Bayliss, K.; Gill, K.; O'Sullivan, C.; Whitechurch, M. (Brain (London, England : 1878), 2012)
The peripheral manifestations of the inherited neuropathies are increasingly well characterized, but their effects upon cranial nerve function are not well understood. Hearing loss is recognized in a minority of children with this condition, but has not previously been systemically studied. A clear understanding of the prevalence and degree of auditory difficulties in this population is important as hearing impairment can impact upon speech/language development, social interaction ability and educational progress. The aim of this study was to investigate auditory pathway function, speech perception ability and everyday listening and communication in a group of school-aged children with inherited neuropathies. Twenty-six children with Charcot-Marie-Tooth disease confirmed by genetic testing and physical examination participated. Eighteen had demyelinating neuropathies (Charcot-Marie-Tooth type 1) and eight had the axonal form (Charcot-Marie-Tooth type 2). While each subject had normal or near-normal sound detection, individuals in both disease groups showed electrophysiological evidence of auditory neuropathy with delayed or low amplitude auditory brainstem responses. Auditory perception was also affected, with greater than 60% of subjects with Charcot-Marie-Tooth type 1 and greater than 85% of Charcot-Marie-Tooth type 2 suffering impaired processing of auditory temporal (timing) cues and/or abnormal speech understanding in everyday listening conditions.